The efficacy and toxicity of afatinib in advanced EGFR-positive non-small-cell lung cancer patients after failure of first-generation tyrosine kinase inhibitors: a systematic review and meta-analysis - Zhang, Yaxiong; Miao, Siyu; Wang, Fang; Fang, Wenfeng; Chen, Gang; Chen, Xi; Yan, Fang; Huang, Xiaodan; Wu, Manli; Huang, Yan; Zhang, Li (Journal of Thoracic Disease, 2017)
Background: The first generation epidermal growth factor receptor-tyrosine kinase inhibitors (EGFR-TKIs), gefitinib and erlotinib, have become the standard first-line treatment for non-small-cell lung cancer (NSCLC) patients with EGFR mutation. However, there was no pooled analysis focused on the usage of the second-generation TKI, afatinib, in advanced EGFR-positive NSCLC patients after failure of first generation TKIs. Therefore, a meta-analysis was conducted to solve the above question. Methods: Electronic databases were searched for eligible literatures. ORR (objective response rate), DCR (disease controlled rate), PFS (progression-free survival), OS (overall survival) and primary grade 3/4 adverse events were pooled with the corresponding 95% confidence interval using R software. Sensitivity analyses and heterogeneity were quantitatively evaluated. Results: A total of 545 EGFR-positive patients were available for analysis from five studies after detailed screening from 909 relevant studies. The pooled ORR and DCR of afatinib in EGFR-positive patients after failure of the first generation EGFR-TKIs were 0.12 (0.08–0.19) and 0.60 (0.53–0.68), respectively. Besides, the 6 m-PFS rate, 1 y-PFS rate and 6 m-OS rate were 0.26 (0.22–0.30), 0.08 (0.06–0.10) and 0.74 (0.56–0.86). The grade 3/4 rate of diarrhea and that of skin deformity were 0.23 (0.10–0.46) and 0.14 (0.05–0.33), respectively. Sensitivity analyses revealed similar results with lower heterogeneity. Conclusions: Considering the efficacy, toxicity and current availability, afatinib could be a therapeutic option for advanced EGFR mutated NSCLC patients after the failure of 1st-generation TKIs.